Flutuação populacional de artrópodes em cultivos de soja BT e Não-BT - Carneiro, Felipe de Sousa (Universidade Federal de São Carlos, 2021)
Transgenic cultivars use containing Bacillus thuringiensis (Bt) technology has increased significantly in recent years in Brazil, especially in soybean. Even if the technology has provided highly beneficial to production systems, the topic is the scene of great discussions and uncertainties related to the effects that Bt toxin cause to natural enemies and other non-target arthropods present in the crops. In the present study, a population survey of arthropods presents in Bt with glyphosate resistance technology and non-Bt without glyphosate resistance technology soybean cultivars was carried out using the beating cloth sampling method, aiming to evaluate the population fluctuation of natural enemies and pests. It was observed from data collection no significant difference between the three species of natural enemies observed in the samplings, however it was evidenced that not only target pests of the Bt technology were affected, but also some species of secondary pests showed significant difference between the treatments, for example the bettle Maecolaspis calcarisera. Therefore, Bt technology proved to be efficient to be used as an alternative strategy in Integrated Pest Management, being selective to natural enemies and mostly affecting only arthropods targeted by this technology.
Population fluctuation of arthropods in BT and Non-BT in soybean crops
Keywords: Plantas Transgênicas; Glycine max; Manejo Integrado de Pragas; Inimigos Naturais; Pragas; Transgenic Plants; Integrated Pest Management; Natural enemies; Pests; CIENCIAS AGRARIAS::AGRONOMIA